Sunday

April 20, 2014

April 20, 2014

Posted by **Anonymus** on Tuesday, March 1, 2011 at 5:23pm.

- Trig -
**agrin04**, Wednesday, March 2, 2011 at 6:25amsec^4(x) - tan^4(x) =

= (1 + tan^2(x))^2 - tan^4(x)

= 1 + 2tan^2(x) + tan^4(x) - tan^4(x)

= 1 + 2tan^2(x)

QED

**Related Questions**

calculus (check my work please) - Not sure if it is right, I have check with the...

pre calculus 2 - use the fundamental trig. Identities to simplify tan^4x+2tan^2x...

trig - Write the expression and evaluate. There is only one answer whIch should ...

trig 26 - simplify to a constant or trig func. 1. sec ²u-tan ²u/cos ²v+sin ²v ...

trig - Verify that each trigonometric equation is an identity tan^2+1/sec Î± =...

trig...again - gahh i cant figure this one out either. you have you verify the ...

Trig - Proving Identities: 2 columns (tan + cot)^2 = sec^2 + csc^2 I'm having ...

Math - Prove Trig. Identities 1. sec è (sec è - cos è)= tan^2 è 2. tan^2 è (1 + ...

Trig. - sec^2xcotx-cotx=tanx (1/cos)^2 times (1/tan)-(1/tan)=tan (1/cos^2) times...

trig - prove: (tan x + sec x)^2 = 2sec^2 x + 2tan x sec x - 1